Investigation of the success of monitoring slow motion landslides using Persistent Scatterer Interferometry and GNSS methods - Hastaoglu, K. O.; Poyraz, F.; Turk, T.; Yilmaz, I; Kocbulut, F.; Demirel, M.; Sanli, U.; Duman, H.; Sanli, F. Balik (TAYLOR & FRANCIS LTD, 2018)
The purpose of this study is to determine deformations in landslide areas with two methods, Persistent Scatterer Interferometry (PSI) and GNSS (Global Navigation Satellite System). In the Koyulhisar landslide area, 53 GNSS points were established throughout the region. Velocity values for these points are three-dimensional. In addition, TerraSAR-X SAR (Synthetic Aperture Radar) images were processed with Stanford Method for Persistent Scatterers software. Slip surfaces of the landslide region in the direction of the line of sight were calculated from PSI in addition to one-dimensional velocity values. These values were compared to GNSS data converted to the same format. GNSS was found more effective for tracking local deformations based on point data while PSI was better at areal movements. Using both methods together is the most effective in this region because there are small local movements independent of regional movements.
Keywords: PSI; GNSS; Landslides; Monitoring; NORTH ANATOLIAN FAULT; SAR INTERFEROMETRY; INSAR; GPS; DEFORMATION; TURKEY; Engineering; Geology; Remote Sensing